Intraminority Gay Community Stress and Coping Responses Among Gay and Bisexual Men in Taiwan - Yen, Cheng-Fang; Chang, Yu-Ping; Wu, Chia-Fen (Journal of homosexuality, 2025)
A proportion of gay and bisexual men (GBM) experience worse mental health when they encounter stress from problems within the gay community. This qualitative study examined the dominant standards held in the gay community in Taiwan, the intraminority-community stress experienced by GBM, and the strategies that GBM adopt to cope with such stress. Data from open and in-depth interviews with 26 GBM were subject to reflexive thematic analysis. The results found that appearance, sexual satisfaction, wealth and social status, being a member of gay groups, and youth were valued in the gay community in Taiwan. These standards resulted in a variety of stress responses, including concerns about not fitting in, diminished self-confidence, feelings of frustration due to unattainable standards and challenges in interpersonal relationships. The strategies adopted to cope with such stress involved acceptance and adherence, passive acceptance, rational thinking and critique, mental resilience, mutual support, and efforts to question and challenge norms. Our findings can provide mental health professionals with key insights into the intraminority gay community stress and coping responses in GBM.